2013
DOI: 10.1007/s00109-013-1108-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases from breast cancer: lessons from experimental magnetic resonance imaging studies and clinical implications

Abstract: Breast cancer that has metastasized to the brain presents difficult clinical challenges. This diagnosis comes with high mortality rates, largely due to complexities in early detection and ineffective therapies associated with both dormancy and impermeability of the blood-brain barrier (BBB). Magnetic resonance imaging (MRI) is the current gold standard for diagnosis and assessment of brain tumors. It has been used clinically to investigate metastatic development as well as monitor response to therapy. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
(59 reference statements)
1
25
0
Order By: Relevance
“…This failure is mostly attributed to the lack of drug penetration through the blood-brain barrier (BBB). However, although the BBB is relevant for large molecules, such as trastuzumab, the blood-tumor barrier (BTB) is leakier, permitting drug delivery to BMs, especially at later stages of the disease (3, 4). Consistent with the BTB being leaky, both preclinical and clinical studies have shown some accumulation of anti-HER2 drugs in BMs (5, 6), but it remains unclear whether adequate drug concentrations are achieved in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…This failure is mostly attributed to the lack of drug penetration through the blood-brain barrier (BBB). However, although the BBB is relevant for large molecules, such as trastuzumab, the blood-tumor barrier (BTB) is leakier, permitting drug delivery to BMs, especially at later stages of the disease (3, 4). Consistent with the BTB being leaky, both preclinical and clinical studies have shown some accumulation of anti-HER2 drugs in BMs (5, 6), but it remains unclear whether adequate drug concentrations are achieved in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…So the blood‐tumor barrier (BTB) is leakier than the intact BBB. If chemotherapy and radiation therapy were combined, it could allow delivery in brain lesions especially at advanced stages of disease 35. Nowadays, numerous techniques are developed to improve the delivery of therapeutics across the BBB, just like chemical modification of the drug,36 temporary disruption of the BBB 37 and so on.…”
Section: The Bbb Penetration and Bmmentioning
confidence: 99%
“…Although the patient had been in remission from breast cancer for more than six years, and [1][2][3]. From this case, we can learn that the breast cancer may have been eradicated from the original source, but we should always be suspicious of the malignancy re-emerging in other parts of the body.…”
Section: Discussionmentioning
confidence: 99%